Characterization by Quantitative Serum Proteomics of Immune-Related Prognostic Biomarkers for COVID-19 Symptomatology - Villar, Margarita; Urra, José Miguel; Rodríguez-del-Río, Francisco J.; Artigas-Jerónimo, Sara; Jiménez-Collados, Natalia; Ferreras-Colino, Elisa; Contreras, Marinela; de Mera, Isabel G. Fernández; Estrada-Peña, Agustín; Gortázar, Christian; de la Fuente, José (Frontiers in Immunology, 2021)
The COVID-19 pandemic caused by SARS-CoV-2 challenges the understanding of factors affecting disease progression and severity. The identification of prognostic biomarkers and physiological processes associated with disease symptoms is relevant for the development of new diagnostic and therapeutic interventions to contribute to the control of this pandemic. To address this challenge, in this study we used a quantitative proteomics together with multiple data analysis algorithms to characterize serum protein profiles in five cohorts from healthy to SARS-CoV-2-infected recovered (hospital discharge), nonsevere (hospitalized), and severe (at intensive care unit; ICU) cases with increasing systemic inflammation in comparison with healthy individuals sampled prior to COVID-19 pandemic. The results showed significantly dysregulated proteins and associated biological processes and disorders associated to COVID-19. These results corroborated previous findings in COVID-19 studies and highlighted how the representation of dysregulated serum proteins and associated BPs increases with COVID-19 disease symptomatology from asymptomatic to severe cases. The analysis was then focused on novel disease processes and biomarkers which were correlated with disease symptomatology. To contribute to translational medicine, results corroborated the predictive value of selected immune-related biomarkers for disease recovery (Selenoprotein P, SELENOP; Serum paraoxonase/arylesterase 1, PON1), severity (Carboxypeptidase B2, CBP2) and symptomatology (Pregnancy zone protein, PZP) using protein-specific ELISA tests. Our results contributed to the characterization of SARS-CoV-2-host molecular interactions with potential contributions to the monitoring and control of this pandemic by using immune-related biomarkers associated with disease symptomatology.